회전익 항공기 전륜착륙장치 단속거동 현상 개선연구 - 최재형; 장민욱; 이윤우; 윤종진; Choi, Jae Hyung; Chang, Min Wook; Lee, Yoon-Woo; Yoon, Jong Jin (한국항공운항학회지, 2017)
The Nose Landing Gear(NLG) of Rotary Wing Aircraft is an essential equipment in Landing System for pilot to perform a flight mission. It supports the fuselage at ground and absorbs the impact from the ground when landing, thereby, these functions sustain operational capability for pilot and crew. However, the A aircraft caused stick-slip behavior when it was stationed on the ground. Therefore, this paper summarizes pilot comment in operation which are classified by cause of occurrence and the troubleshooting process about each comment. It also describes design improvements which was derived from troubleshooting and suggests verification results of flight test.